Effectiveness of the Inquiry Based Learning Model Based on Mobile Learning on Students' Creative Thinking Skills: A Meta-Analysis - Suyatmo Suyatmo; Via Yustitia; Tomi Apra Santosa; Fajriana Fajriana; Unan Yusmaniar Oktiawati (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the effect of the inquiry-based learning model based on Mobile Learning on Students' Creative Thinking Skills. This type of research is quantitative research with meta-analysis methods. The data source comes from analysis of national and international journals. The process of searching for data sources through the Google Scholar, ERIC, DOAJ, Wiley, Taylor of Francis and Plos ONE databases. Inclusion criteria are data sources from national and international journals indexed by SINTA; Scopus, WOS, DOAJ and EBSCO, Research must be related to inquiry models, mobile learning and critical thinking skills, Journals must be published in 2017-2023 and have a value (r), (t), or F N â‰¥ 25. Research results of 18 studies explains that the inquiry-based learning model based on mobile learning has a significant effect on students' creative thinking skills (z = 6.713; p < 0.001; CI 95% (0.784; 1.206). The effect size in this study is high criteria (rRE = 0.885). These findings show the application of mobile learning-based inquiry learning models has a major effect on students' creative thinking skills.